Evaluation of a dual-room sliding gantry CT concept for workflow optimisation in polytrauma and regular in- and outpatient management. Issue 1 (January 2015) - Frellesen, Claudia; Boettcher, Marie; Wichmann, Julian L.; Drieske, Martina; Kerl, J. Matthias; Lehnert, Thomas; Nau, Christoph; Geiger, Emmanuel; Wutzler, Sebastian; Ackermann, Hanns; Vogl, Thomas J.; Bauer, Ralf W.
Highlights: A sliding gantry trauma room CT solution facilitates significantly faster polytrauma management. Faster and more efficient resumption of regularly scheduled patients due to a two room solution is supported. Sliding gantry CT achieves the same patient throughput as two separate conventional CT devices. Abstract: Objectives: To reveal the impact on workflow from introducing a dual-room sliding gantry CT to the trauma room for polytrauma and regularly scheduled in- outpatients with regard to efficiency and degree of capacity utilisation. Materials and methods: Time analysis was performed for 30 polytrauma patients each in 2 different trauma room settings, the new trauma room comprising a sliding gantry CT, the old one a stationary single-room CT. Complete trauma room and diagnostic workup times were manually measured and compared for both groups. In a third scenario, the number of CT scans performed with one single sliding gantry CT and the two-room concept was compared to the number of CT scans performed on two separate regular CT units in a 5 days clinical routine sample. Results: Patients demographics and type of CT examinations were comparable for all patient groups. The median time from patient arrival in the trauma room until beginning of CT scanning was 6 min shorter for the sliding gantry CT group (21 vs.15 min). Sliding gantry CT embedded in a two-room solution achieved 252 CT scans in 5 working days, compared to 250 CT scans on two separate regular CT units with the same man power. Conclusions: Sliding gantry CT in the trauma room allows for significant time saving in the diagnostic workup of polytrauma patients and faster resumption of the regular in- outpatient's CT schedule is possible. With the same man power, the dual-room solution is able to generate the same throughput as two separate CT units.